Channel characteristics and planform dynamics of the lower Niger River, Niger Delta Basin (1985–2015) - Akana, Tombra; Adeigbe, Olubunmi (Geology, Geophysics and Environment, 2020)
This study used repeat satellite imagery and Geographic Information System analysis to assess the planform dynamics along the length of the lower Niger River Valley from Onitsha city to the coast between 1985 and 2015. The aim is to understand the altered dynamics and its plausible causes in this data-poor region. Analyses revealed that the Niger River has undergone change corresponding to enhanced instability in terms of an increased rate of erosion. In the study area, a change was observed from 3.7% of deposition in the first 10 years (1985–1995) to 3.9% of erosion in the next 10 years (1995–2005) and 4.7% of erosion in the last 10 years (2005–2015). Total erosion over the 30-year period (1985–2015) in the delta was calculated on 4.8%. The river channel has migrated toward the east in the upper and lower reaches while the mid-section of the channel is migrating towards the west. The east river bank is observed to be more unstable compared to west bank line through the study period. The maximum shifts identified were 3.35 km of deposition in 10 years (1985–1995), 3.31 km of erosion in the next 10 years (1995–2005), and another substantial erosional shift of 3.35 km in the next 10 years (2005–2015). Avulsion rates gradually moved from −42.1 m∙year−1 (1985–2005, segment F) to 100.2 m∙year−1 (1985–1995, segment D), large deposition in the first 10 years. Total avulsion rates of the delta in the last 30 years (1985–2015) has pointed on erosion (−2.2 m∙year−1). The altered dynamics observed would likely threaten the future of the fragile lower river system environment and raise concerns for operators with infrastructure within the Niger Delta.